Prevalence of obstructive sleep apnoea in metabolic syndrome - Dubey, A. P.; Rajput, Ashok K.; Suhag, Virender; Sharma, Durgesh; Kandpal, Ajay; Keisham, Roshlin (International Journal of Advances in Medicine, 2017)
Background: The prevalence of both OSA and metabolic syndrome is increasing worldwide, in part linked to the epidemic of obesity. Beyond their epidemiologic relationship, growing evidence suggests that OSA may be causally related to metabolic syndrome. We are only beginning to understand the potential mechanisms underlying the OSA-metabolic syndrome interaction. Objectives were to study the clinical prevalence of obstructive sleep apnoea in metabolic syndrome; and to find risk factors associated with obstructive sleep apnoea (OSA). Methods: 50 patients attending various OPDs of a tertiary care research and referral hospital and found to have metabolic syndrome on the basis of NCEP criteria were selected. These patients were subjected to overnight polysomnography. Parameters such as apnea-hypopnoea index (AHI), respiratory efforts related arousals (RERA), minimum SpO2, pulse rate, blood pressure, and ECG were monitored throughout the study. Results: Central obesity was found in 34 patients, xanthelasmas in 12 patients and xanthomas in 08 patients. Pitting type of pedal oedema was noted in 14 patients. Epworth sleepiness score (ESS) was calculated in all the patients by interviewing them before the polysomnography. Most of the patients have ESS Score more than 11.03 out of 50 patients were found to have AHI<5.20 patients were found to have moderate AHI (AHI 15-30) whereas 22 were found to have severe AHI. Conclusions: Polysomnography provides a valuable tool to access non symptomatic sleep disordered breathing at an early stage in patients with metabolic syndrome.